2002
DOI: 10.1002/1522-2683(200205)23:9<1328::aid-elps1328>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of a highly sulfated cyclodextrin for the simultaneous chiral separation of amphetamine-type stimulants by capillary electrophoresis

Abstract: We investigated the simultaneous chiral separation of nine amphetamine type stimulants (dl-norephedrine, dl-norpseudoephedrine, dl-ephedrine, dl-pseudoephedrine, dl-amphetamine, dl-methamphetamine, dl-methylenedioxyamphetamine (MDA), dl-methylenedioxymethamphetamine (MDMA), and dl-methylenedioxyethylamphetamine (MDEA)) by capillary electrophoresis using highly sulfated gamma-cyclodextrin (SU(XIII)-gamma-CD) as a chiral selector. Three different approaches using SU(XIII)-gamma-CD with 50 mM phosphate background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…62 Due to very similar chemical structure of the amphetamines, (±)-pseudoephedrine has also been used as a precursor for the clandistine production of methamphetamine and related illicit drugs. 63 The serum halflife of (±)-pseudoephedrine is 5-8 hrs and about one-half of the dosage taken is excreted in the urine. 64…”
Section: Application Of Optimized Mekc-ms Conditions For Sensitive Psmentioning
confidence: 99%
“…62 Due to very similar chemical structure of the amphetamines, (±)-pseudoephedrine has also been used as a precursor for the clandistine production of methamphetamine and related illicit drugs. 63 The serum halflife of (±)-pseudoephedrine is 5-8 hrs and about one-half of the dosage taken is excreted in the urine. 64…”
Section: Application Of Optimized Mekc-ms Conditions For Sensitive Psmentioning
confidence: 99%
“…In recent years, anionic CDs were used in the chiral analysis of some ATS by CE. [11][12][13][14] Lurie et al 11 reported a method using sulfated(XIII)-γ-CD etc. High chiral separations of ATSs were gained (e.g.…”
Section: K2k1}mentioning
confidence: 99%
“…A number of CE methods have been utilized for the chiral separation of amphetamines in seized drugs etc. [13][14][15][16][17][18] and in urine. [19][20][21][22][23][24] However, these methods for amphetamines in urine require a procedure of extraction from urine and are unsatisfactory with respect to the need for rapid analyses.…”
Section: Introductionmentioning
confidence: 99%